A novel method to store methane by forming hydrate in the high water-oil ratio emulsions. (1st February 2023) - Mu, Liang; Tan, Qiqi; Li, Xianlong; Zhang, Qingyun; Cui, Qingyan
Abstract: Natural gas (NG) storage in the form of clathrate hydrates gains much attention due to their non-explosive and eco-friendly characteristics. This study developed a novel method to store methane by forming hydrate in the high water cut (40–100 vol%) emulsions, in which an excellent anti-agglomerant (AA) cocamidopropyl dimethylamine (CDA) was employed in combination with sorbitan monododecanoate (Span 20). The CH4 storage achieved 151.1 v/vh (volume ratio of gas to hydrate, the theoretical value is 172 v/vh ) in the 60 vol% systems within 60 min, which was significantly increased than the hydrate formation tests in the presence of single (Span 20, CDA) and combined additives (Span 20 coupled with tetrabutylammonium bromide (TBAB), fatty alcohol polyoxyethylene ether, N = 3 (AEO-3), l -tryptophan (L-Trp), sodium dodecyl sulfate (SDS), respectively). The effect of CDA concentration, initial pressure and stirring speed on hydrate formation was investigated. The fastest hydrate growth lasted 20 min for the test with 1000 rpm and the CH4 storage attained 151.9 v/vh . The maximum gas uptake achieved 166.2 v/vh within 2 h for the test with 8.2 MPa. No foams were observed in hydrate dissociation and the tests can be repeatable. Highlights: High water cut (40–100 vol%) emulsions were selected to form hydrate for methane storage. A promising anti-agglomerant (CDA) greatly improved the gas uptake and hydrate formation kinetics with the help of Span 20. The maximum gas uptake achieved 166.2 v/vh in the 60 vol% water cut emulsions. The fastest hydrate formation was accomplished within 20 min and no foams were observed in dissociation.